Tickner, J. A.; Sjoberg, L. (Eds.) (2013). Feminism and International Relations. Conversations about the Past, Present and Future, 1st Edition, Routledge, 274 páginas - Busconi, Antonella (2019)
Fil: Fil: Busconi, Antonella. Universidad Nacional de Rosario; Argentina